New contributions to the knowledge of Chinese flea beetle fauna (I): Gansuapteris new genus and Primulavorus new genus (Coleoptera: Chrysomelidae: Galerucinae) - Ruan, Yong-Ying; Konstantinov, Alexander S.; Prathapan, K. D.; Yang, Xing-Ke (Zootaxa, 2017)
Two new genera and species of flea beetles (Gansuapteris gen. nov., Primulavorus gen. nov., Gansuapteris fulvus sp. nov. and Primulavorus maculata sp. nov.) from south-west China are described and illustrated. Distinguishing features of the new genera and their allies are discussed.